Is There A Reliable Way of Knowing? - I. U. Gwunireama; Victor Chizi Ihunda (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2021)
The human quest for knowledge is not a mere quest for information that may probably be true, but an anxious quest for certainty. What then, does it mean to know? Is knowledge possible? What are the sources of our knowledge? This paper deals with some of these recurring epistemological questions and, more precisely, the question: Is there a reliable way of knowing? To claim to know requires that the object of our knowledge is not only true but also that the source from which such a knowledge claim originates is at least reasonably reliable. Therefore, in our response to the question of the possibility of a reliable way to knowledge, we argued that it would be reasonable to think of the reliability of our sources of knowledge not in absolute terms, but comparatively and depending on the context of a given claim to knowledge, because certain sources or kinds of knowledge, if subjected to critical analysis, may simply be more reliable than others. Thus, in light of the numerous challenges associated with certain sources or kinds of knowledge, the virtue of epistemic humility demands that we acknowledge that no single source or kind of knowledge is devoid of challenges that come in the way of its reliability. This work concludes that there is no reliable way to know. Outside of that context, each of our sources of knowledge falls short of being reliable and is capable of misleading us in our quest for knowledge.